METHOD OF ACQUISITION AND TERMINATION OF JUDICIAL OFFICE IN SERBIA IN THE SECOND HALF OF THE 19TH CENTURY - Чворовић, Зоран Р (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
From the viewpoint of the way of acquisition and termination of the judicial service, judges in Serbia passed a long road from ordinary civil servants that were acquiring and losing their position solely based on the will of the minister of justice, to independent judges with guaranteed tenure appointed on recommendation from the highest courts and dismissed by decision of the highest courts in the country. The path, however, was not straight-line, neither in terms of normative solutions nor in terms of political and social temptations. The Law on Judges from 1881 which regulated the Judiciary of the Principality of Serbia on the principles of judicial consistency, competence and financial security, introduced for the first time the method of electability (co-optation) of judges by judicial collegiums in the Serbian judiciary. At the same time, this Law completely disempowered Minister of Justice of the right to decide on the termination of the judge’s office and handed it over to the highest court in the country - the Cassation court. The significance of the formal guarantees of judicial independence, which has been ensured since 1881 by specific procedure of acquisition and termination of judicial office, became questionable due to both “pestilent” touch between judges and politics, but also for substantial number of judges who took judicial independence as judicial irresponsibility.